Sustainable management of coffee berry disease and leaf rust co-infection: a systematic review of deterministic models - Usa Wannasingha Humphries; Porntip Dechpichai; Alhassan Ibrahim; Muhammad Waqas; Boobphachard Chansawang; Gabor Kiss; Angkool Wangwongchai (MethodsX, 2025)
Colletotrichum kahawae, the cause of Coffee Berry Disease (CBD), poses a significant threat to global coffee production, especially in Africa, with potential implications for Latin America and Asia.This systematic review evaluates 24 models of CBD, Coffee Leaf Rust (CLR), Coffee Berry Borer (CBB), and co-infection of CBD with CLR, as well as strategies for optimal control.It concludes the relevance of the basic reproduction number (R0) for forecasting outbreaks and the benefits of employing a combination of control measures.Despite advancements, limitations still exist, including the need for empirical validation and the consideration of vector-mediated transmission in co-infection models. Future research should integrate GIS, climate data, and field trials for validation, model vector-host-pathogen interactions, and assess cost-effective strategies for smallholder farmers to ensure sustainable coffee production.